Analisis Perbandingan Harga Pokok Produksi antara Metode Perusahaan dan Metode Full Costing pada UMKM Cafe Kopi Senusa Indonesia: Comparative Analysis of Cost of Production between the Company Method and the Full Costing Method in MSMEs Cafe Kopi Senusa Indonesia - Nabilla Ahmad; Aurellia Putri Natasha; Muhammad Ikhtiar; Pasha Achmad Rabbani; Rika Aulia (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
This study aims to analyze how the MSME Cafe Senusa Kopi Indonesia calculates its Cost of Goods Manufactured (COGM). To review this issue thoroughly, the study applies a descriptive qualitative method to ensure all production cost components are clearly identified. The results indicate that the internal COGM calculation previously used by the cafe was suboptimal, as it only included specific costs. The calculated components only consisted of Raw Material Costs of Rp2,142,500, Direct Labor Costs of Rp1,800,000, and Variable Manufacturing Overhead of Rp469,500, resulting in a COGM of Rp2,941 per cup for a total production of 1,500 cups. Conversely, when re-analyzed using the Full Costing method, adjustments were made by including previously omitted Fixed Manufacturing Overheads, namely electricity costs of Rp1,000,000 and shop house rent of Rp2,500,000. The inclusion of these costs caused the total production cost to surge to Rp7,912,000, thereby producing a much more accurate and realistic COGM value of Rp4,794 per cup.